2019
DOI: 10.1111/jar.12583
|View full text |Cite
|
Sign up to set email alerts
|

Examining determinants of lifestyle interventions targeting persons with intellectual disabilities supported by healthcare organizations: Usability of the Measurement Instrument for Determinants of Innovations

Abstract: Implementation of innovations aimed at persons with intellectual disabilities can be complex in healthcare organizations and lifestyle settings outside the organization, such as a community or sports centre, the local supermarket or settings related to the social environment of the person with intellectual disabilities, which are supporting these individuals (Fleuren, Paulussen, van Dommelen, Abstract Background: Due to complex processes of implementation of innovations aimed at persons with intellectual disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These interviews were structured by using determinants of MIDI; see Table 1 for an overview of the data collection method that was used for each determinant. Where MIDI is originally a quantitative method, during the consultation meetings we used it as an interview guide, to ensure that relevant domains of implementation were discussed, as is done in earlier studies [ 35 , 38 ]. Questions were presented on-screen one by one and the professionals answered the questions in an interactive program (Teams Forms or Mentimeter), after which the answers were discussed and elaborated upon in the group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interviews were structured by using determinants of MIDI; see Table 1 for an overview of the data collection method that was used for each determinant. Where MIDI is originally a quantitative method, during the consultation meetings we used it as an interview guide, to ensure that relevant domains of implementation were discussed, as is done in earlier studies [ 35 , 38 ]. Questions were presented on-screen one by one and the professionals answered the questions in an interactive program (Teams Forms or Mentimeter), after which the answers were discussed and elaborated upon in the group.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the experts involved in the development studies found that most determinants were generic. Third, since its publication in 2014, MIDI has been validated, used and tested in process evaluations of different types of healthcare interventions [35][36][37][38].…”
Section: Methodsmentioning
confidence: 99%
“…Maps of health needs are undoubtedly a tool enabling such measurements and analysis of health data, whereas, according to many authors, the essential tool supporting the planning and coordination of healthcare, used for communication with the patient, is electronic medical documentation [42][43][44][45][46]. This documentation is also necessary for the effective use of telemedicine and e-health mobile solutions in health service delivery [80][81][82][83]. However, digitalization may create some difficulties in extreme situations and during disasters in obtaining the necessary authorization to access patients' data and should be considered in the early planning phases.…”
Section: Discussion Challenges and Recommendationsmentioning
confidence: 99%
“…It is based on a systematic review, a Delphi panel [29] and empirical studies [6], which resulted in 29 factors. MIDI has been successfully applied in different settings and innovations [30][31][32]. MIDI briefly describes each code and illustrates the code with examples.…”
Section: Coding and Analysismentioning
confidence: 99%